Difference in Rupture Risk Between Familial and Sporadic Intracranial Aneurysms: An Individual Patient Data Meta-analysis. (30th November 2021) - Zuurbier, Charlotte C.M.; Mensing, Liselore A.; Wermer, Marieke J.H.; Juvela, Seppo; Lindgren, Antti E.; Koivisto, Timo; Jääskeläinen, Juha E.; Yamazaki, Tomosato; Molenberg, Rob; van Dijk, J. Marc C.; Uyttenboogaart, Maarten; Aalbers, Marlien; et al.
Abstract : Background and Objectives: We combined individual patient data (IPD) from prospective cohorts of patients with unruptured intracranial aneurysms (UIAs) to assess to what extent patients with familial UIA have a higher rupture risk than those with sporadic UIA. Methods: For this IPD meta-analysis, we performed an Embase and PubMed search for studies published up to December 1, 2020. We included studies that (1) had a prospective study design; (2) included 50 or more patients with UIA; (3) studied the natural course of UIA and risk factors for aneurysm rupture including family history for aneurysmal subarachnoid haemorrhage and UIA; and (4) had aneurysm rupture as an outcome. Cohorts with available IPD were included. All studies included patients with newly diagnosed UIA visiting one of the study centers. The primary outcome was aneurysmal rupture. Patients with polycystic kidney disease and moyamoya disease were excluded. We compared rupture rates of familial vs sporadic UIA using a Cox proportional hazard regression model adjusted for PHASES score and smoking. We performed 2 analyses: (1) only studies defining first-degree relatives as parents, children, and siblings and (2) all studies, including those in which first-degree relatives are defined as only parents and children, but not siblings. Results: We pooled IPD from 8 cohorts with a low and moderate risk of bias. First-degree relatives were defined as parents, siblings, and children in 6 cohorts (29% Dutch, 55% Finnish, 15% Japanese), totaling 2, 297 patients (17% familial, 399 patients) with 3, 089 UIAs and 7, 301 person-years follow-up. Rupture occurred in 10 familial cases (rupture rate: 0.89%/person-year; 95% confidence interval [CI] 0.45–1.59) and 41 sporadic cases (0.66%/person-year; 95% CI 0.48–0.89); adjusted hazard ratio (HR) for familial cases 2.56 (95% CI 1.18–5.56). After adding the 2 cohorts excluding siblings as first-degree relatives, resulting in 9, 511 patients, the adjusted HR was 1.44 (95% CI 0.86–2.40). Discussion: The risk of rupture of UIA is 2.5 times higher, with a range from a 1.2 to 5 times higher risk, in familial than in sporadic UIA. When assessing the risk of rupture in UIA, family history should be taken into account.